Development of Problem-Based Physics E-Book on The Topics of Work And Energy to Improve Students' Conceptual Understanding and Digital Literacy - Artanti, Francisca Happy; Widiatmono, Restu; Jumadi, Jumadi (FKIP Universitas Lampung, 2025)
This study aims to develop an electronic book (e-book) based on the Problem-Based Learning (PBL) approach to enhance students' conceptual understanding and digital literacy on the topic of work and energy. Responding to the growing demand for interactive and student-centered learning media in physics education, the e-book is designed to serve as a learning resource that fosters engagement in problem-solving and critical thinking. The research adopts the ADDIE development model, comprising Analysis, Design, Development, Implementation, and Evaluation, and applies a quantitative approach using a one-group pretest-posttest design. Participants in this study were tenth-grade students from State Senior High School 9, Yogyakarta. Data were collected through the use of the developed e-book, conceptual understanding tests, digital literacy questionnaires, and student response surveys. Validators rated the e-book as “highly valid” and suitable for use. The implementation results showed a significant improvement in students' conceptual understanding, with an N-gain score of 0.71, which falls into the high category. Additionally, there was an improvement in digital literacy, with an N-gain score of 0.66, which also falls into the high category. The effectiveness of this e-book was also tested using a T-test and showed significant improvements before and after learning for both variables. Additionally, students responded positively, finding the e-book engaging, easy to access, and beneficial in supporting their learning process. These preliminary findings indicate that the PBL-based e-book has the potential to be an effective learning tool for high school physics education. Keywords: e-book, problem-based learning, work and energy, conceptual understanding, digital literacy.